Technicolor coupled models - Natale, A. A. [UNESP]; Doff, A. (My University, 2019)
When technicolor (TC), QCD, extended technicolor (ETC) and other interactions become coupled through their different Schwinger-Dyson equations, the solution of these equations are modified compared to those of the isolated equations. The change in the self-energies is similar to that obtained in the presence of four-fermion interactions, but without their ad hoc inclusion in the theory. In this case the TC and QCD self-energies decrease logarithmically with the momenta, which allows us to build models where ETC boson masses can be pushed to very high energies, and do not lead to undesirable flavor changing interactions. Viable TC models may be built along this line including a necessary horizontal symmetry. The different fermionic mass scales are dictated by the different strong interactions. Pseudo-Goldstone bosons acquire large masses in this class of models.